2007
DOI: 10.1197/j.aem.2006.09.052
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison Trial of Case‐based Learning versus Human Patient Simulation in Medical Student Education

Abstract: HPS training offers no advantage to CBL as measured by medical student performance on a chest pain objective structured clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…For example, Schwartz et al reported that human patient SIM showed no significant difference in medical student performance (21). However, they noted that baseline academic achievement differences in their study groups occurred despite random assignment, and this may have affected their results (21). By comparing each student's individual SIM score with their individual LEC score, we eliminate confounding due to baseline differences in knowledge, intellect, or test-taking skills.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Schwartz et al reported that human patient SIM showed no significant difference in medical student performance (21). However, they noted that baseline academic achievement differences in their study groups occurred despite random assignment, and this may have affected their results (21). By comparing each student's individual SIM score with their individual LEC score, we eliminate confounding due to baseline differences in knowledge, intellect, or test-taking skills.…”
Section: Discussionmentioning
confidence: 95%
“…By comparing each student's individual SIM score with their individual LEC score, we eliminate confounding due to baseline differences in knowledge, intellect, or test-taking skills. Schwartz et al also noted that students studied on their own, outside of prescribed reading and didactics, and "a difference in study habits between the two intervention groups could potentially mask a difference in the efficacy of the educational modalities tested" (21). This study controlled for this issue, as all students had the same amount of "study time," which included only LEC and SIM time.…”
Section: Discussionmentioning
confidence: 99%
“…Students may have a preference for a specific platform, but it may have little influence on performance. 29,30 Conventional wisdom suggests that adapting instruction to students' preferred learning styles should improve their academic performance. However, the literature is mixed and learning preference and learning styles are not consistently associated with academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…"high" vs. "low fidelity simulation") macht den Vergleich unterschiedlicher Studien schwierig. Simulationstraining ging ziemlich konsistent [33,125,126,127,128,129,130,131,132,133,134,135,136], aber nicht generell [137,138,139,140,141,142,143] [187], die Durchführungsfertig-keiten [188], das Selbstvertrauen [189] und die Vertrautheit mit der Umgebung [190] der ALS-Helfer verbessern sowie Fehler im System und bei den Helfern identifizieren [191,192].…”
Section: Simulation Und Training Der Realistischen Wiederbelebungunclassified